KELAYAKAN DAUN BAYAM HIJAU (AMARANTHUS HYBRIDUS L) SEBAGAI HAIR TONIC RAMBUT RONTOK - Fitria, Elsa; Rahmiati, Rahmiati (CHEDS: Journal of Chemistry, Education, and Science, 2023)
Hair loss causes a lack of self-confidence. Hair loss can be caused byhormonal factors and an unhealthy lifestyle. Hair tonic is a type of hair care cosmetic that is useful in nourishing and maintaining healthy hair. Research objectives To analyze how to make green spinach as a hair tonic, to analyze the feasibility of green spinach leaf hair tonic in terms of vitamin C and B vitamins, to determine the feasibility of green spinach leaf hair tonic in terms of organoleptic and hedonic tests of panelists' preferences. This type of research is an experiment. The data analysis technique is descriptive analysis. The results of the study showed that vitamin B in green spinach leaves was 0.1847%/100 gram sample and Vitamin C was 21.56%/100 gram sample. Based on the organoleptic test, the odor indicator obtained 57.1% (less distinctive smell of green spinach leaves), the color indicator obtained 71.42% (greenish yellow), the absorption capacity indicator obtained 57.1% (absorbed). The feasibility of green spinach leaf hair tonic seen from the results of the hedonic test was liked by the observer.